Landscape change in the Icelandic highland: A long-term record of the impacts of land use, climate and volcanism. (15th July 2020) - Eddudóttir, Sigrún Dögg; Erlendsson, Egill; Gísladóttir, Guðrún
Absatract: Agriculture has been practiced in Iceland since settlement ( landnám ; AD 877). This has caused changes in vegetation communities, soil erosion, desertification and loss of carbon stocks. Little data exist regarding vegetation and ecosystems in the Icelandic highland before landnám and therefore the impact of land use over time is poorly understood. The objectives of the study are to examine the timing, nature and causes of land degradation in the highland of Northwest Iceland. Specifically, to determine the resilience of the pre- landnám highland environment to disturbances (i.e. climate cooling and volcanism) and whether land use pressure was of sufficient magnitude to facilitate ecosystem change. A sediment core was taken from the highland lake Galtaból. A chronology for the core was constructed using known tephra layers and radiocarbon dated plant macrofossils. Pollen analysis (vegetation), coprophilous fungal spores (proxy for grazing), and sediment properties (proxies for erosion) were used to provide a high-resolution, integrated vegetation and paleoenvironmental reconstruction. The pre- landnám environment showed resilience to climate cooling and repeated tephra fall. Soon after landnám the vegetation community changed and instability increased, indicated by changes in sediment properties. The pollen and spore record suggest introduction of grazing herbivores into the area after landnám . Following landnám, indicators of soil erosion appear in the sediment properties. Intensification of soil erosion occurred during the 17th century. The Galtaból record clearly demonstrates what can happen in landscapes without adequate management of natural resources and underestimation of landscape sensitivity. Introduction of land use resulted in changes in vegetation communities, loss of resilience and onset of increased soil erosion. Paleoenvironmental reconstructions may inform future decisions on management of the highland by providing baselines for natural variability in the pre- landnám environment. Highlights: The first high-resolution, integrated vegetation and paleoenvironmental reconstruction from the highland environs of Iceland. The pre- landnám environment showed resilience to climate cooling and repeated tephra fall. The pollen and spore record suggest introduction of grazing herbivores into the area after landnám. Following landnám indicators of soil erosion appear in the sediment properties. Intensification of soil erosion occurred during the 17th century.